Drosophila immunity against natural and nonnatural viral pathogens. - Tafesh-Edwards, G.; Eleftherianos, I. (Virology, 2020)
The fruit fly Drosophila melanogaster is extensively used as a model species for molecular biology and genetics. It is also widely studied for its innate immune system to expand our understanding of immune host defenses against numerous pathogens. More precisely, studies using both natural and nonnatural Drosophila pathogens have provided a better perspective of viral infection strategies and immunity processes than any other invertebrate. This has made significant advances in identifying and characterizing the innate immune mechanisms by which hosts can combat viral pathogens. However, in-depth studies on antiviral immunity are still lacking due in part to the narrow research focus on the evolution and conservation of antiviral strategies to combat infections caused by both natural and nonnatural viruses. In this review, we will cover three major areas. First, we will describe the well-characterized antiviral immune mechanisms in Drosophila. Second, we will survey the specific pathways induced by natural viruses that have been studied in Drosophila. Finally, we will discuss the pathways activated by nonnatural viruses, drawing comparisons to natural viruses and giving an unprecedented insight into the virus community of Drosophila that is necessary to understand the evolutionary and immune context needed to develop Drosophila as a model for virus research.